PERANCANGAN SISTEM INFORMASI PENDATAAN DANA BANTUAN DESA MENGGUNAKAN BORLAND DELPHI 7.0 PADA KANTOR KECAMATAN GOMBONG - Dwi Ratna Sari, Fitriani; Hidayat, Irfan (Politeknik Dharma Patria Kebumen, 2018)
The development of science and information technology today is more advanced. In a government agencies and non-government, information systems plays a very important to simplyfyof job. The data collection process of grants at the district office Gombong still manual by using Microsoft Word, so that the collected data results are less than the maximum, less effective time. To solve the problem above, the authors designed a systeminformation of village grants using Borland Delphi 7.0 at the district office gombong. With the system can facilitate the admin to collecting data and making the report of creation grants.